2018
DOI: 10.1002/ece3.4548
|View full text |Cite
|
Sign up to set email alerts
|

The shadow of the past: Convergence of young and old South American desert lizards as measured by head shape traits

Abstract: Convergence is a pervasive phenomenon in the Tree of Life, and evolution of similar phenotypes sharing the same environmental conditions is expected in phylogenetically closely related species. In contrast, contingent factors are probably more influential in shaping phenotypic diversity for distantly related taxa. Here, we test putative convergent evolution of lizard head morphologies among relatively closely related desert dwelling Liolaemus species, and the very distantly related Ctenoblepharys adspersa. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
(75 reference statements)
1
14
1
6
Order By: Relevance
“…Given that our hypothesis is supported by our morphological analyses, we consider the molecular studies of Aguilar-Puntriano et al [66] and the thermal ecology studies of Jiménez-Robles and De la Riva [105] to provide independent evidence that supports our hypothesis. In their research on convergence within the L .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Given that our hypothesis is supported by our morphological analyses, we consider the molecular studies of Aguilar-Puntriano et al [66] and the thermal ecology studies of Jiménez-Robles and De la Riva [105] to provide independent evidence that supports our hypothesis. In their research on convergence within the L .…”
Section: Discussionsupporting
confidence: 74%
“…schmidti )))))). Although somewhat different from our phylogenetic proposal (Fig 1), due in part to a different set of species utilized, the findings of Aguilar-Puntriano et al [66] validate the hypothesis that the lizards of the Tajzara Basin described in this present work represent a new species of the L . montanus group.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…This includes the coastal regions of southern Peru and northern Chile (Valladares et al 2004;Villegas-Paredes et al 2020), as well as southern Brazil (Verrastro et al 2003) and demonstrates a broad adaptive radiation of the genus in the region (Abdala et al 2020). In Peru, 28 species in the genus Liolaemus have been described to date (Chaparro et al 2020; Huamaní-Valderrama et al 2020; Arapa-Aquino et al 2021), although recent phylogenetic analyses have shown that this number is likely an underestimate, given the existence of several undescribed lineages or "candidate species" (Aguilar et al 2017(Aguilar et al , 2018Abdala et al 2020;Huamaní-Valderrama et al 2020).…”
Section: Introductionmentioning
confidence: 99%